Cloverfield [videorecording (DVD)] - Reeves, Matt, 1966-; Caplan, Lizzy, 1982-; Lucas, Jessica, 1985-; Miller, T. J., 1981- (Paramount Home Entertainment, 2008)
Rob is getting ready to leave New York in order to take an executive job at a company in Japan. At his goodbye party in a crowded loft, Rob's brother Jason hands a camcorder to best friend Hud, who proceeds to tape the party over old footage of Rob's ex-girlfriend, Beth. Beth shows up at the party with a new beau, which upsets Rob. Then the unexpected happens: New York is suddenly under attack from a Godzilla-like monster who stomps through midtown, destroying everything and everybody in sight. Rob and his friends take to the streets, but instead of running away with the other evacuees, they head toward the center of destruction so that Rob can rescue an injured Beth.